A disulfidptosis-related lncRNA signature for analyzing tumor microenvironment and clinical prognosis in hepatocellular carcinoma - Zheng, Haishui; Cheng, Jigan; Zhuang, Ziyun; Li, Duguang; Yang, Jing; Yuan, Fan; Fan, Xiaoxiao; Liu, Xiaolong (Frontiers in Immunology, 2024)
Disulfidptosis is a recently identified form of non-apoptotic programmed cell death that distinguishes itself from the classical cell death pathways. However, the prognostic implications of disulfidptosis-related long non-coding RNAs (DRLs) and their underlying mechanisms in hepatocellular carcinoma (HCC) remain largely unexplored. In this study, we leveraged RNA sequencing data and clinical information of patients with HCC from the TCGA database. Through expression correlation and prognostic correlation analyses, we identified a set of top-performing long non-coding RNAs. Subsequently, a 5-DRLs predictive signature was established by conducting LASSO regression analysis. This signature effectively stratified patients into high-and low-risk groups, revealing significant differences in survival outcomes. Further validation using univariate and multivariate Cox regression analyses confirmed that the risk score derived from our signature independently predicted the prognosis of patients with HCC. Moreover, we observed significant disparities in immune cell infiltration and tumor mutation burden (TMB) between the two risk groups, shedding light on the potential connection between immune-related mechanisms and disulfidptosis. Notably, this signature also exhibited predictive value in the context of chemotherapeutic drug sensitivity and immunotherapy efficacy in HCC patients. Finally, we performed experimental validation at both the cellular and patient levels and successfully induced a disulfidptosis phenotype in HCC cells. In general, this multifaceted approach provides a comprehensive overview of DRLs profiles in HCC, culminating in the establishment of a novel risk signature that holds promise for predicting prognosis and therapeutic outcomes in HCC patients.